The effect of exogenous peroxiredoxin 6 on morphofunctional state of isolated rat kidney - A. E. Gordeeva; M. G. Sharapov; V. I. Novoselov (Вестник трансплантологии и искусственных органов, 2021)
Objective: to investigate the role of peroxiredoxin 6 (PRX6) in preserving the morphofunctional state of ischemic isolated kidney during perfusion.Materials and methods. The model of an isolated perfused rat kidney was used. Ischemia time was 5 and 20 minutes, perfusion was 50 minutes. To evaluate the effectiveness of PRX6 at different ischemia times, we used the conventional criteria of kidney function and histological methods.Results. During short warm ischemia times, exogenous PRX6 improves the morphofunctional state of an isolated kidney during perfusion. During this period, the main criteria for functioning of the isolated ischemic kidney reach acceptable values, renal parenchyma is without severe damage. By the end of perfusion, there was an increase in urine flow rate, glomerular filtration rate, fractional glucose reabsorption, urine urea concentration and proportion of primary urine from 1.5 to 2 times compared with the control lesion. At 20-minute ischemia, the isolated kidney can be recognized as non-viable according to the functioning criteria; the positive effect of PRX6 is leveled.Conclusion. The use of recombinant peroxiredoxin 6 for preserving the morphofunctional state of isolated kidneys can be an effective approach in preventing ischemia–reperfusion injury.